PELAKSANAAN PEMEBELAJARAN BERNYANYI SECARA UNISONO DI SMP 22 X 11 KAYU TANAM KABUPATEN PADANG PARIAMAN - Putri Ana Finata; Syeilendra Syeilendra; erfan erfan (FBS Universitas Negeri Padang, 2018)
Abstract This article aims to describe how the implementation of learning singing in unisono in Junior 2 2 x 11 Wood Planting Padang Pariaman. The type of research used a qualitative approach is descriptive method. The object of research is the students who follow the implementation of learning to sing in unison in Junior 2 2 x 11 Wood Planting Padang Pariaman. Instrument in this study is the researchers themselves by means of observation and documentation of the interview. The type of data in this study with data collection, reduction of data, display data, and verification or retrieval conclusion. Data that has been collected is classified, in order to avoid misinterpretation of data. The results showed that the implementation of learning singing in unisono haven't done with good cause is internal and external factors. The internal factor consists of desires, participation, and attention, and external factor seen from teachers and parents. The wishes of the student in following the implementation process of learning singing unisono in very low. Attention students in learning have followed a less good attention. And of most students there who follow the learning process are singing unisono with the mean seriously. Keywords: Implementation of Learning Singing In Unisono